A versatile platform of corn stalk-based membranes for high performance of oil/water separation. (April 2023) - Wang, Jie; Zhou, Jiale; Zhai, Rui; Zang, Wenhan; Wang, Bo; Liu, Xiangchen; Cong, Xiaori; Xiang, Qiong; Wang, Cong; Yu, Cunming; Teng, Chao; Ma, Xiaoyan
Abstract: Due to the discharge of oily wastewater, there is an urgent need to develop advanced oil/water separation materials having the characteristic of versatility and cost-efficiency in an eco-friendly manner. In this work, we used natural corn stalks as a raw material to prepare a versatile platform for oil/water separation. The corn stalks without treatment can separate efficiently light oil/water mixtures with a high flux, which is attributed to underwater superoleophobicity and interconnective porous structure. In addition, an enlarged membrane was prepared by combining multiple corn stalks to achieve a higher flow rate of oil/water separation (30 mL/min) relative to a single corn stalk. More interestingly, the local corn stalk can be used directly to separate oil/water mixtures through removing part of stem marrow. After modifying with polydimethylsiloxane (PDMS) and hydrophobic silicon dioxide (SiO2 ), a corn stalk@PDMS@SiO2 membrane (CPSM) was obtained to achieve heavy oil/water separation owing to the wetting state transition from superhydrophilicity to superhydrophobicity. The XPS measurement reveals the chemical information of superhydrophiobic coating. Moreover, the CPSM could successfully separate water-in-1, 2-dichloroethane emulsion and selectively absorb oils. The developed corn stalk-based materials originate from nature, are simple to prepare, and realize efficient separation for multiple types of oil/water mixtures. Highlights: Natural corn stalks were used to prepare a versatile platform for oil/water separation. Corn stalks were used directly to separate light oil/water mixtures. The CPSM achieved heavy oil/water separation and selectively absorbed oils. Superwetting CPSM for separating W/O emulsion was designed.